Serological and molecular epidemiological study on swine influenza in Zambia. Issue 4 (16th November 2021) - Harima, Hayato; Okuya, Kosuke; Kajihara, Masahiro; Ogawa, Hirohito; Simulundu, Edgar; Bwalya, Eugene; Qiu, Yongjin; Mori‐Kajihara, Akina; Munyeme, Musso; Sakoda, Yoshihiro; Saito, Takehiko; Hang'ombe, Bernard M.; et al.
Abstract: Influenza A viruses (IAVs) cause highly contagious respiratory diseases in humans and animals. In 2009, a swine‐origin pandemic H1N1 IAV, designated A(H1N1)pdm09 virus, spread worldwide, and has since frequently been introduced into pig populations. Since novel reassortant IAVs with pandemic potential may emerge in pigs, surveillance for IAV in pigs is therefore necessary not only for the pig industry but also for public health. However, epidemiological information on IAV infection of pigs in Africa remains sparse. In this study, we collected 246 serum and 605 nasal swab samples from pigs in Zambia during the years 2011–2018. Serological analyses revealed that 49% and 32% of the sera collected in 2011 were positive for hemagglutination‐inhibition (HI) and neutralizing antibodies against A(H1N1)pdm09 virus, respectively, whereas less than 5.3% of sera collected during the following period (2012–2018) were positive in both serological tests. The positive rate and the neutralization titres to A(H1N1)pdm09 virus were higher than those to classical swine H1N1 and H1N2 IAVs. On the other hand, the positive rate for swine H3N2 IAV was very low in the pig population in Zambia in 2011–2018 (5.3% and 0% in HI and neutralization tests, respectively). From nasal swab samples, we isolated one H3N2 and eight H1N1 IAV strains with an isolation rate of 1.5%. Phylogenetic analyses of all eight gene segments revealed that the isolated IAVs were closely related to human IAV strains belonging to A(H1N1)pdm09 and seasonal H3N2 lineages. Our findings indicate that reverse zoonotic transmission from humans to pigs occurred during the study period in Zambia and highlight the need for continued surveillance to monitor the status of IAVs circulating in swine populations in Africa.